Latex interpenetrating polymer networks based on polyacrylates and polystyrene. I. Synthetic variations - Nagarajan P; Mital C K; Trivedi M K (Journal of Applied Polymer Science, 1996)
Two different acrylic copolymeric seeds (with 0 and 6;methacrylic acid), having very high variation in the hydrophilicity, were used to develop latex interpenetrating polymer networks (LIPNs) with polystyrene as polymer II, to study the effect of the mode of monomer II addition, such as continuous monomer addition and absorption method/swelling the seed with monomer II, followed by polymerization. Linear combination of the two polymers were also prepared to understand the above effects on the final properties such as the glass transition temperature, hardness, and tensile strength of the different samples prepared. The results showed that the addition of styrene monomer by the absorption method and the increase in hydrophilicity of the seed improved the mixing of the two polymers, thus resulting in producing LIPNs possessing broad glass transition with high strength and hardness.
Keywords: Interpenetratin network; Latex; Polyacrylate